Koreksi Gaya Berat Akibat Curah Hujan Pada Pengukuran Gaya Berat Mikro Antar-Waktu Lapangan Panas Bumi Kamojang 2006-2007 - Zaenudin, Ahmad (BERKALA FISIKA, 2010)
Shallow groundwater level changes cause seasonal gravity anomaly. Changes in groundwater level is directly related to rainfall, when heavy rainfall, groundwater level rises rapidly and then declined gradually. Gravity anomaly due to the season is important to take into account noise. Changes in groundwater level due to rainfall is calculated using empirical equations, and the Gravity response calculated using the approach of an infinite Bouguer slab correction by entering the porosity factor. The rainy season in the Kamojang geothermal field occur between November to June and dry season between July to October. The highest rainfall in 24 hours occurred on December 8 by 75 mm. From the empirical calculations showed that changes in groundwater level due to rainfall period November 2006-June 2006 amounted to -1.502 m and July 2007-June 2006 amounted to +0.396 m. Based on the approach slab Bouguer corrected gravity anomaly not to cause inter-time respectively -18.89 and +5.98 mikrogal mikrogal for porosity of 30%. Changes in groundwater level is negative (a reduction of groundwater) caused gravity anomaly time inter-negative, and vice versa. Correction of the gravity anomaly due to inter-time rainfall should not be ignored because of the gravity anomaly at the time inter-geothermal field is usually small. Key words: rainfall, groundwater level, inter-period gravity anomaly